Dampak Implementasi PSAK 71 Pada PT. Adira Dinamika Multi Finance, TBK. - Aulia Khasify; Ary Natalina; Supiningtyas Purwaningrum (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine the calculation of the Allowance for Impairment Losses (CKPN), the impact and suitability of applying PSAK 71 at PT. Adira Dinamika Multi Finance, Tbk. This study uses a qualitative approach with descriptive research methods, by analyzing the application of PSAK 71 related to CKPN at PT. Adira Dinamika Multi Finance, Tbk. from 2019 to 2021. The results of this study indicate that, the calculation of Impaired Credit Loss (ECL) uses the Expected Credit Loss (ECL) Method in accordance with PSAK 71. The impact of implementing PSAK 71 increases the amount of Allowance for Impairment Loss on credit due to several accounts in the financial statements affected by the transition to PSAK 71 namely financing receivables, finance lease receivables and deferred tax assets, thereby affecting the company's capital by decreasing retained earnings. Covid-19 pandemic PT. Adira Dinamika Multi Finance Tbk. has implemented Credit Restructuring to reduce high CKPN balances in 2020 and 2021. In addition, there is no significant impact on changes in the classification of financial assets and PT. Adira Dinamika Multi Finance, Tbk. has implemented PSAK 71..